Correction: Publisher Correction: Wave energy budget analysis in the Earth’s radiation belts uncovers a missing energy - A. V. Artemyev (Nature Portfolio, 2018)
Nature Communications 6: Article number: 7143 (2015); Published: 15 May 2015; Updated: 26 March 2018 The original HTML version of this Article had an incorrect article number of 8143; it should have been 7143. This has now been corrected in the HTML; the PDF version of the Article was correct from the time of publication.